DNA fragmentation is higher in spermatozoa with chromosomally unbalanced content in men with a structural chromosomal rearrangement. (19th June 2013) - Perrin, A.; Nguyen, M. H.; Bujan, L.; Vialard, F.; Amice, V.; Guéganic, N.; Douet‐Guilbert, N.; De, M.; Morel, F.
Summary It has been previously shown that men with chromosomal structural abnormality had a higher rate of sperm DNA fragmentation. We studied 11 male carriers of a chromosomal structural abnormality (seven with a balanced reciprocal translocation, three with a Robertsonian translocation, one with a pericentric inversion) to determine whether spermatozoa with unbalanced chromosomes were more likely to have fragmented DNA. A sequential method combining analysis of DNA fragmentation using the TUNEL assay followed by analysis of meiotic segregation by fluorescent in situ hybridization was performed on the same spermatozoa. A statistically significant higher number of spermatozoa with unbalanced chromosomal content were found to have fragmented DNA for each man. The rate of spermatozoa with DNA fragmentation was higher than the rate of those without fragmented DNA in particular modes of segregation. Our findings provide a better understanding of the mechanisms involved in male infertility ascribable to chromosomal structural abnormality.